Which Chile do we want to inherit to our children? - Rivera, Raúl (Base Diseño e Innovación, 2014)
Since our inception as independent republic, Chileans have demonstrated a strong dedication towards progress. Along the last couple of centuries, this dedication has approached us more and more to modernity, by staying at the leading edge of Latin America in the majority of key social and economic indicators. With the gateway to prosperity at sight, our current challenge is to end shaping an innovative, entrepreneur, inclusive, and fair Chile, able of harnessing the talents of all Chilean people to achieve and sustain a high level of prosperity and social development.